The Analysis of Differences in Translating Arabic Texts into Indonesian Using ChatGPT and Google Translate - Amaliyah, Nurul; Muflihah, Muflihah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Abstract In the last few years, technological advances in the current digital era have shown very rapid development. One of them is in translating foreign languages, such as translating Arabic into Indonesian. ChatGPT and Google Translate are human-made intelligence that helps people when translating. This research aims to determine and analyze the differences in translation of Arabic texts into Indonesian using artificial intelligence technology, namely ChatGPT Google Translate. The results of this research are that there are differences in the translation using both and several errors were found. Therefore, the translation requires proofreading to avoid confusion in the meaning of a particular word.Keywords: Translation; ChatGPT; Google Translate.